2015
DOI: 10.1186/s12995-015-0058-5
|View full text |Cite
|
Sign up to set email alerts
|

A technical support tool for joint range of motion determination in functional diagnostics - an inter-rater study

Abstract: BackgroundThe examination of joint range of motion (RoM) is part of musculo-skeletal functional diagnostics, used, for example, in occupational examinations. Various examination methodologies exist that have been optimized for occupational medical practice, which means they were reduced to the most necessary and feasible measures and examinations for efficiency and usability reasons. Because of time constraints in medical examinations in occupational settings, visual inspection is commonly used to quantify joi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 29 publications
3
39
0
Order By: Relevance
“…However, results were comparable to reported reliability and agreement results of other studies assessing the reliability and agreement of ST or humerothoracic range of motion measurements by means of inertial sensors in healthy persons. Schiefer et al [18] reported a within-session ICC for humerothoracic abd-adduction of 0.96 in healthy persons which is in line with the reported within-session ICC-values in this study during functional task performance in persons with AC [18]. Bouvier et al [17] described the performance of standardized analytical movements in healthy persons; there were lower intra-operator reliability results for humerothoracic abd-adduction and ext-internal rotation than for flexion-extension [17].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…However, results were comparable to reported reliability and agreement results of other studies assessing the reliability and agreement of ST or humerothoracic range of motion measurements by means of inertial sensors in healthy persons. Schiefer et al [18] reported a within-session ICC for humerothoracic abd-adduction of 0.96 in healthy persons which is in line with the reported within-session ICC-values in this study during functional task performance in persons with AC [18]. Bouvier et al [17] described the performance of standardized analytical movements in healthy persons; there were lower intra-operator reliability results for humerothoracic abd-adduction and ext-internal rotation than for flexion-extension [17].…”
Section: Discussionsupporting
confidence: 87%
“…We furthermore aim to formulate recommendations regarding parameter selection when using inertial sensor movement analysis to evaluate treatment efficacy and follow up progress. It is hypothesized that, in line with previous research [14][15][16][17][18], in general good reliability and agreement results will be found for ST, GH, and elbow joint range of motion assessment, but that reliability and agreement results will depend on the complexity of the assessment movement task.…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…According to the Downs and Black checklist [27], 12 studies were of substantial quality [30][31][32][33][34][35][36][37][38], 10 of moderate quality [39][40][41][42][43][44][45][46][47][48] and one of low quality [49]. Within the studies on kinematics in healthy persons, the methodological quality was 60% on average (range between 42-75%).…”
Section: Methodological Qualitymentioning
confidence: 99%
“…In OCRA this corresponds to about 45 for both flexion and extension, while a flexion angle of 30 and an extension angle of 40 is used in RAMP II. For flexion without external pressure (Barter, Emanuel, and Truett 1957), the value of 45 used in OCRA corresponds to about 54-73% of ROM (Houy 1983;Boone and Azen 1979;Ryu et al 1991;AAOS 1988;Schiefer et al 2015;Marshall, Mozrall, and Shealy 1999). Because the ROM was reported to decrease by up to 27% when gripping objects (Gehrmann, Kaufmann, and Li 2008), 30 as used in RAMP II may better reflect the 50% of ROM for flexion of a working population for jobs involving the gripping of large and small objects.…”
Section: The Assessment Criteriamentioning
confidence: 99%